Implementation of Lean-Based QCC Method for Reducing Rework and Enhancing Process Reliability in Supply Pump Testing - Alfaruq, Muhammad Amiruddin; Abikusna, Setia; Hanif, Muhammad Kaysan (JTTM : Jurnal Terapan Teknik Mesin, 2026)
Rework in component testing processes represents a significant source of waste and process instability in heavy-equipment remanufacturing. In supply pump testing, unstandardized procedures and equipment variability often lead to repeated testing and extended lead time. This study examines the effectiveness of a Lean-based Quality Control Circle (QCC) approach in stabilizing the supply pump testing process and reducing rework. An industrial case study with an action-research approach was conducted in a heavy-equipment remanufacturing environment from March to July 2025. The QCC 8-Step methodology, integrated with Lean principles, was applied to identify root causes, implement corrective actions, and establish standardized testing procedures. Performance was evaluated using a before–after comparison based on testing records, operational logs, and operator feedback. The findings indicate that no rework cases were recorded after implementation compared to a baseline rework rate of 35%. Average testing time per unit decreased by approximately 50%, while operator satisfaction increased from 30% to 89%. These results demonstrate that integrating Lean and QCC effectively reduces defect-related waste and improves process reliability through standardization. The study contributes to applied industrial research by positioning Lean-based QCC as a practical framework for enhancing process reliability and supporting sustainable and digitally ready manufacturing systems.